2008
DOI: 10.1534/genetics.107.086074
|View full text |Cite
|
Sign up to set email alerts
|

Polytene Chromosomal Maps of 11 Drosophila Species: The Order of Genomic Scaffolds Inferred From Genetic and Physical Maps

Abstract: The sequencing of the 12 genomes of members of the genus Drosophila was taken as an opportunity to reevaluate the genetic and physical maps for 11 of the species, in part to aid in the mapping of assembled scaffolds. Here, we present an overview of the importance of cytogenetic maps to Drosophila biology and to the concepts of chromosomal evolution. Physical and genetic markers were used to anchor the genome assembly scaffolds to the polytene chromosomal maps for each species. In addition, a computational appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
258
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(286 citation statements)
references
References 167 publications
19
258
2
Order By: Relevance
“…Synpipe (Bhutkar et al 2006) output helped to assign assembly scaffolds to one of six Muller elements and join contiguous scaffolds together. The inferred ordered scaffolds were largely 1658 A. Bhutkar et al consistent with the genetic and physical map data (Schaeffer et al 2008). The assembled and ordered scaffolds provided a unique opportunity to study how gene order changes among species of Drosophila by the processes of inversion and transposition, using the study of adjacency information at conserved linkage breakpoints.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…Synpipe (Bhutkar et al 2006) output helped to assign assembly scaffolds to one of six Muller elements and join contiguous scaffolds together. The inferred ordered scaffolds were largely 1658 A. Bhutkar et al consistent with the genetic and physical map data (Schaeffer et al 2008). The assembled and ordered scaffolds provided a unique opportunity to study how gene order changes among species of Drosophila by the processes of inversion and transposition, using the study of adjacency information at conserved linkage breakpoints.…”
Section: Introductionsupporting
confidence: 61%
“…Synpipe accommodates for contig and scaffold gaps in the assembly by identifying homologous elements that might either fall in unsequenced assembly gaps or lie on the edges of sequenced segments or on small assembly fragments. The resulting Synpipe Drosophila data set has been used for breakpoint analysis, a comparative study of chromosomal rearrangements between species, multispecies alignment and orthology refinement, and for mapping and orienting scaffolds onto the Drosophila Muller elements or chromosome arms (Schaeffer et al 2008).One protein isoform, that with the 59-most translation start site annotation, was chosen for each predicted gene in the reference set. Syntenic blocks were computed as segments of the assembly where orthologs shared the gene order of the reference species while allowing for gaps and localized scrambling due to micro-inversions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cytological studies as well as comparative studies of the genome sequences from related species revealed that genome reorganization is widespread among taxa (for example, Krimbas and Powell, 1992;Newman et al, 2005;Clark et al, 2007;Ferguson-Smith and Trifonov, 2007;Schaeffer et al, 2008). Structural variation ranging from chromosome fusions to paracentric inversions underlies the detected reorganization.…”
Section: Introductionmentioning
confidence: 99%